2015
DOI: 10.1016/j.jaapos.2014.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Binocular iPad treatment for amblyopia in preschool children

Abstract: Background Recent experimental evidence supports a role for binocular visual experience in the treatment of amblyopia. The purpose of this study was to determine whether repeated binocular visual experience with dichoptic iPad games could effectively treat amblyopia in preschool children. Methods A total of 50 consecutive amblyopic preschool children 3–6.9 years of age were assigned to play sham iPad games (first 5 children) or binocular iPad games (n = 45) for at least 4 hours per week for 4 weeks. Thirty (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 28 publications
2
118
4
2
Order By: Relevance
“…Indeed, 85% (23 of 27) of children played at least 75% of prescribed treatment compared with 44% (20 of 45) in the Tetris game study. 15 Furthermore, some children at the 4-week visit in our study had already completed all game levels or had reached 100% fellow eye contrast.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, 85% (23 of 27) of children played at least 75% of prescribed treatment compared with 44% (20 of 45) in the Tetris game study. 15 Furthermore, some children at the 4-week visit in our study had already completed all game levels or had reached 100% fellow eye contrast.…”
Section: Discussionmentioning
confidence: 87%
“…1517 Contrast rebalancing allows the child to overcome interocular suppression and experience binocular vision while playing the games. 14,18 Poor compliance in 24% to 38% of children indicated that the games developed for our prototype iPad platform (Tetris and Pong) were not engaging.…”
mentioning
confidence: 99%
“…These approaches may reactivate latent binocular pathways by reducing inhibitory interactions, boosting attenuated excitatory function, and/or shifting the synaptic modification threshold in favor of potentiation (reviewed in Hess & Thompson, 2015). For example, recent studies have found that both amblyopic preschool children and adults can show enhanced improvements in visual and motor function by playing dichoptic iPad or iPod games (Hess et al, 2011; Birch et al, 2015; Vedamurthy et al, 2015; Webber et al, 2016). Since the lack of binocular function is a key risk factor for persistent amblyopia, the development of new binocular training strategies may have a substantial impact on improving acuity and recovering stereopsis (reviewed in Levi et al, 2015).…”
Section: Environmental and Behavioral Treatmentsmentioning
confidence: 99%
“…10,11 Treatment regimens designed to alleviate suppression via repeated exposure to contrast-balanced binocular stimuli improve visual acuity in amblyopic adults 12 and amblyopic children. 1316 Thus, severity of suppression may be a useful baseline and outcome measure in clinical amblyopia research.…”
mentioning
confidence: 99%